The Role of Platelet Cell Surface P-Selectin for the Direct Platelet-Tumor Cell Contact During Metastasis Formation in Human Tumors - Fabricius, Hans-Åke; Starzonek, Sarah; Lange, Tobias (Frontiers in Oncology, 2021)
Mammalian platelets, devoid of nuclei, are the smallest cells in the blood stream. They are essential for hemostasis, but also transmit cell signals that are necessary for regenerative and generative processes such as inflammation, immunity and tissue repair. In particular, in malignancies they are also associated with cell proliferation, angiogenesis, and epithelial-mesenchymal transition. Platelets promote metastasis and resistance to anti-tumor treatment. However, fundamental principles of the interaction between them and target cells within tumors are complex and still quite obscure. When injected into animals or circulating in the blood of cancer patients, cancer cells ligate platelets in a timely manner closely related to platelet activation either by direct contact or by cell-derived substances or microvesicles. In this context, a large number of different surface molecules and transduction mechanisms have been identified, although the results are sometimes species-specific and not always valid to humans. In this mini-review, we briefly summarize the current knowledge on the role of the direct and indirect platelet-tumor interaction for single steps of the metastatic cascade and specifically focus on the functional role of P-selectin.